RENCANA STRATEGIS BISNIS RSU PKU MUHAMMADIYAH GUBUG GROBOGAN - Aisyah Lahdji; Firman Pribadi (Universitas Muhammadiyah Yogyakarta, 2014)
This research is to approach the problem of operational research through descriptive analysis, the Strategic Planning Service Delivery at Muhammadiyah Gubug Hospital (RSMG) Year 2014-2018. The results showed the necessity developed RSMG Services Strategic Plan. Business Strategy Plan should be made with reference to the seven selected strategy resulting from the Focus Group Discussion (FGD based on the results of the analysis of strengths, weaknesses, peluangan, and threats. Required a strong commitment from all employees to implement strategic planning RSMG hospital. In order to improve the quality of human resources, RSMG need to do education and training, providing scholarships for education specialist, general practitioner, and increasing cooperation with specialist partners. Other than that necessary to increase the number / bed capacity and improved quality of care that the utilization of health services provided by RSMG more optimal.